Monitorização de pressão intracraniana por método não invasivo, em mulheres que fazem uso de contraceptivo oral - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
ntracranial Pressure (ICP) can present alterations whenever there is an imbalance among its three components: Cerebrospinal fluid (CSF), the circulating blood and parenchymatous component. In contrast, oral contraceptives present as adverse reactions the cardiovascular and thromboembolic risks, which are factors that may be elevating ICP. Based on this, the present study aimed to verify if the Oral Contraceptive has any correlation with the PIC increase, due to cardiovascular and thromboembolic risks that it may cause. A case-control study was performed, composed by 38 women, which included 18 women that use Oral Contraceptive and 20 women that do not use it (control group). Data were collected through an extracranial sensor that allows to evaluate cranial deformation, where the curve of non-invasive intracranial pressure is registered. It was observed that women in childbearing age use to incorporate habits that elevate cardiovascular and thromboembolic risks, mainly for those who use combined oral contraceptives. Thus, the method of non-invasive ICP monitoring allows to measure an altered ICP, even for patients who have not presented an apparent symptom yet, and provide an early identification of a disease.
Keywords: Contraceptivo oral; risco cardiovascular; Pressão Intracraniana; Trombose Venosa; Oral Contraceptive; cardiovascular risk; Intracranial Pressure; Venous Thrombosis; CNPQ::CIENCIAS DA SAUDE::FARMACIA